PERLIDUNGAN HUKUM TERHADAP DEBITOR DALAM PERJANJIAN PINJAM UANG MELALUI PINJAMAN ONLINE ILEGAL MENURUT UNDANG UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Utama, Ari Putra; Kuncoro, Cipto; Hudi, Mohammad (LAW Specialist Jurnal Ilmiah Hukum, 2024)
Illegal online money lending (Pinjol) has not only a positive impact but also a negative impact. The large number of customer concerns related to various things, such as collections by debt collectors from Pinjol Ilegal, causing debtors (customers) to use threatening words, is something that customers (debtors) often encounter. Therefore, there is a need for legal protection for the methods used by Illegal Pinjol parties. This research aims to examine whether online loans (Pinjol) are a special form of lending and borrowing agreement in the Civil Code (KUH Perdata) as well as legal protection for Pinjol debtors (customers) according to the Information and Electronic Transactions Law. This research is normative legal research using a statutory approach and a conceptual approach. Sources of legal materials consist of primary, secondary and non-legal legal materials. Legal materials are taken by conducting library research. Analysis of legal materials is carried out by citing relevant articles of legislation, while the opinions of scholars are quoted to serve as a theoretical basis for answering the main problem. Based on the results and discussion, it can be concluded that loans are a special form of lending and borrowing in the Civil Code, because there is a differentiating element, namely that the lender and recipient of the loan do not meet face to face and the media used uses an electronic application that has been provided by the borrower. Legal protection by Law Number 11 of 2008 for debtors (customers) can use suggestions for civil lawsuits or criminal means through the courts or use alternative dispute resolution channels through arbitration.